2019
DOI: 10.15252/embj.201899558
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐omics identify xanthine as a pro‐survival metabolite for nematodes with mitochondrial dysfunction

Abstract: Aberrant mitochondrial function contributes to the pathogenesis of various metabolic and chronic disorders. Inhibition of insulin/IGF‐1 signaling (IIS) represents a promising avenue for the treatment of mitochondrial diseases, although many of the molecular mechanisms underlying this beneficial effect remain elusive. Using an unbiased multi‐omics approach, we report here that IIS inhibition reduces protein synthesis and favors catabolism in mitochondrial deficient Caenorhabditis elegans. We unveil that the lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 55 publications
(141 reference statements)
8
21
0
Order By: Relevance
“…Consistent with previous studies, in the present study, we found that exogenously supplemented intermediates of purine metabolism, e.g., uric acid in food, significantly prolonged the life span of the nematodes. In support of our findings, other researchers have also found that supplementing the food of C. elegans with other purine metabolic intermediates, including allantoin [46] and xanthine [47], significantly extended the life span of worms. These results reveal that purine metabolic intermediates play an important role in the regulation of aging and that endogenous purine metabolites may be developed into potential strategies for the prevention and treatment of aging and age-related diseases.…”
Section: Agingsupporting
confidence: 91%
“…Consistent with previous studies, in the present study, we found that exogenously supplemented intermediates of purine metabolism, e.g., uric acid in food, significantly prolonged the life span of the nematodes. In support of our findings, other researchers have also found that supplementing the food of C. elegans with other purine metabolic intermediates, including allantoin [46] and xanthine [47], significantly extended the life span of worms. These results reveal that purine metabolic intermediates play an important role in the regulation of aging and that endogenous purine metabolites may be developed into potential strategies for the prevention and treatment of aging and age-related diseases.…”
Section: Agingsupporting
confidence: 91%
“…Previous studies have identified that older subjects have higher glutamine compared to younger subjects (Kaiser et al, 2005), confirming our observation. The classifier also identified that elevated xanthine was associated with increased LTL, confirming a multi-omics study that showed xanthine as a pro-survival metabolite with aberrant mitochondrial function (Gioran et al, 2019). Similarly, our model also suggested that elevated beta-sitosterol is increased with longer LTL.…”
Section: Metabolic Predictors Of Ltlsupporting
confidence: 85%
“…AMPK activation, glycolysis upregulation, and mitochondrial biogenesis have been documented in mouse and C . elegans OXPHOS disease models (Gioran et al, 2019; Haynes et al, 2007; Kuhl et al , 2017; Nargund et al, 2015; Viscomi et al, 2011; Wredenberg et al, 2002). Importantly, pharmacological activation of AMPK by AICAR partially corrects COX deficiency (Viscomi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%